The effect of new biological products based on Novochizol on the condition of spring common wheat crops - E. A. Orlova; N. P. Bekhtold; A. B. Shcherban; V. V. Fomenko (Зерновое хозяйство России, 2025)
The purpose of the current work was to identify the efficiency of new biological complex products prepared on the basis of Novokhizol (NVKhZ) with chitosan and Siberian pine bark extract (SPBE) in protecting spring common wheat from root rot and obligate pathogens (powdery mildew, brown rust) in the forest-steppe of the Ob region, and also to establish their effect on yield elements. The trials were carried out with the spring wheat variety ‘Novosibirskaya 29’ in the field of SibNIISR – branch of the ICG SB of RAS (Novosibirsk) in 2023–2024. The method of application of the products was pre-sowing seed treatment and treatment of vegetative plants. There has been established an efficiency of NVKhZ + SPBE against common root rot. The development of the disease on the roots on average over two years decreased from 21.5 to 3.95 %, the biological efficiency of the product was 81.7 %. There has been found that the use of biological products on vegetative plants reduced the damage of plants by obligate pathogens more than pre-sowing seed treatment. Seed treatment with products contributed to an increase in plant height by 8.7 % with NVKhZ + Chitosan and by 6.8 % with NVKhZ + SPBE, root length by 36.3 % with NVHZ + Chitosan, by 22 % with NVKhZ + SPBE and plant biomass by 17.6 %. There has been found a positive effect of Novochizol compositions on the formation of productive stems, a length of the main spike, a number of kernels per main spike, and kernels per plant. There has been established and statistically proved a positive effect of the tested products on crop yields. On average, over the years of study, plant productivity in variants with biological products has exceeded control values by 1.2 times.